1999
DOI: 10.1007/bf02358329
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption fibres based on graft copolymers: Fabrication and properties. A review

Abstract: Scientific concepts concerning the characteristics of graft polymerization to oriented polymeric materials and p~lymer-anal~g transf~rmati~ns ~f the graft p~lymer were elab~rated based ~n systematic studies. The principles of fabrication of sorption-active fibre materials Of different ~,pes based on graft copolymers and the most important directions of their use were formulated.The consequences of human technological activity has sharply worsened the environmental situation, making environmental protection an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8]. These facts were also attributed to the effect of steric factors [8].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8]. These facts were also attributed to the effect of steric factors [8].…”
mentioning
confidence: 94%
“…Experiments on amination of PGMA chains grafted onto the surface of polymer fi bers by reactions of these chains with aliphatic polyamines also showed that the density of the incorporated amino groups decreased with an increase in the length of the reacting polyamine molecule [4][5][6][7][8]. In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Among the known ways to obtain chemisorption fibers, the method based on the graft polymerization and chemical transformation in the polymer chains is the most promising [3]. This is because modification of a finished fiber is a simpler technological process, compared with that in which fibrous chemisorbents are obtained by synthesis of copolymers with functionally active groups and then fibers are formed.…”
mentioning
confidence: 98%
“…Methods based on graft polymerization of ionogenic monomers to fibrous materials and polymer-analog transformations of graft copolymers are especially effective. The use of these methods allowed developing the principles of technology for fibrous complexes of different functional composition [6][7][8]. The positive experience in obtaining amine-containing chemisorbents from graft copolymers with polyglycidyl methacrylate (PGMA) makes the use of graft copolymers of polycaproamide and polymethyl methacrylate (PCA-PMMA) attractive for fabricating fibrous sorbents of acid character.…”
mentioning
confidence: 99%